how do you solve for m in equation x(m+8)+y(m-5)=z(m-4) if x+y-z doesnt equal 0


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

how do you solve for m in equation x(m+8)+y(m-5)=z(m-4) if x+y-z doesnt equal 0

solve for m

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

Solving square-root equations (basic) (video) | Khan Academy


We're asked to solve for x. So we have the square root of the entire quantity 5x squared minus 8 is equal to 2x. Now we already have an expression under a radical ...
Read More At : www.khanacademy.org...

Solving Quadratic Equations by Factoring | Purplemath


... " before we make any attempt to solve the quadratic equation by ... So I'll set the factors equal to 12 and solve to get x = 10 and x = 9 ... Solve x 2 – 4 = 0.
Read More At : www.purplemath.com...

Equation - Wikipedia


Linear equations have the form ax + b = 0, where a and b are parameters. To solve ... are equal, the scale balances ... coordinates x and y satisfy the equation x 2 ...
Read More At : en.wikipedia.org...

3 Ways to Solve Two Step Algebraic Equations - wikiHow


How to Solve Two Step Algebraic Equations. ... To solve a two step algebraic equation, all you have to do is ... If there is no number following an x, assume it is x + 0.
Read More At : www.wikihow.com...

Systems of Linear Equations - Math Is Fun


Systems of Linear Equations . ... Solve these two equations: x + y = 6 ... Anywhere on that line d is equal to 0.2t. at t=5 and d=1, the equation is true ...
Read More At : www.mathsisfun.com...

SparkNotes: Quadratics: Graphing Parabolas


A summary of Graphing Parabolas in 's Quadratics. ... Graphing y = x 2. We have ... starting with x = 0, y increases by 1, 3, 5, 7, …. As x ...
Read More At : www.sparknotes.com...

The Slope of a Straight Line | Purplemath


The Slope of a Straight Line. ... plug them into the line equation, and solve for each corresponding y-value. If, ... If you think I'm wrong, ...
Read More At : www.purplemath.com...

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

How do I solve for "w" and (1-w) in equation w x 2.5907 + (1-w) x 1.9234

How do I solve for "w" and (1-w) in equation w x 2.5907 + (1-w) x 1.9234 I need to solve for w and then (1-w) That is NOT an equation, it is only an expression. Notice that there is no equal sign and no value that the expression is equal to. Until we have a complete equation, there is no
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x when (.182+x)/(.106-2x)=3.24

solve for x when (.182+x)/(.106-2x)=3.24 Im trying to solve for x its for a chemistry equation but i need to solve for x using the quadratic equation and i dont know which equals a b and c to find x. ************************** You can't solve this with the quadratic formula, because there is no x^2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how do you solve an equation with an equal sign with a slash through the middle

The equal sign with a slash through it means "not equal to." 2 + 7 ≠ 10    Two plus seven is not equal to ten. As for how to solve the equation, it depends on what the equation is, what it represents.
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve this system of equations using substitutioin: -4x+y=6, -5-y=21

- 4x + y = 6 - 5x - y = 21   To do this we need to rearrange one of the equations. It doesn't matter which one you choose to rearrange but I will choose the first.    - 4x + y = 6 Let's add '4x' to both sides of the equation so that we have an equation in the
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 t
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

2x=3(x-4)=2(x-3)

2x=3(x-4)=2(x-3) How can I solve this? You can't. Even though it is possible to string together multiple equalities, that requires ALL of them to be equal. In this string, the second may in fact be considered to be equal, and you could use the first and second quantities to calculate a value for x.
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

i need the answer for these questions

Part 1 Newton’s Method for Vector-Valued Functions Our system of equations is, f1(x,y,z) = 0 f2(x,y,z) = 0 f3(x,y,z) = 0 with, f1(x,y,z) = xyz – x^2 + y^2 – 1.34 f2(x,y,z) = xy –z^2 – 0.09 f3(x,y,z) = e^x + e^y + z – 0.41 we can think of (x,y,z) as a vector
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve the system: 5x-10y+4z=-73; -x+2y-3z=19; 4x-3y=5z=-42

solve the system: 5x-10y+4z=-73; -x+2y-3z=19; 4x-3y=5z=-42 1)  5x - 10y + 4z = -73 2)  -x +  2y - 3z =  19 3)  4x -  3y + 5z = -42 Equation three had "=5z" so I changed the equal sign to a plus sign. It happens a lot; the shift key doesn't register, so what w
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Y=-4X+3 AND 4Y + X =-1

Not quite sure what you want me to do with these, but i will solve for y in both cases. Then set them equal to eachother and solve for the variables. y = -4x + 3 4y + x = -1 Must get this into y= form. 4y = -x -1           Now we can set the two equations eq
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1739 seconds